2017
DOI: 10.1111/nmo.13161
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal‐regulated kinase activation in the spinal cord contributes to visceral hypersensitivity induced by craniofacial injury followed by stress

Abstract: These data indicate that ERK1/2 activation contributes to the visceral hypersensitivity evoked by craniofacial inflammation pain combined with stress. The results may provide a new therapeutic avenue for alleviating overlapping pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Here, we successfully establish IBS-D animal model after challenging with different stresses, providing a strong evidence to indicate that stresses are causative factors for IBS-D. In response to stresses, many inflammatory cytokines and related signaling pathways are activated, which can affect the function of intestinal mucosa with increasing intestinal permeability or visceral hypersensitivity and eventually result in IBS-D symptoms [ 24 26 ], rather than damage the structure of intestinal mucosa. In line with these observations, our results also demonstrate that inflammatory factors, such as IL-8, TNFα, and MyD88 are significantly increased in the serum of IBS-D rats.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we successfully establish IBS-D animal model after challenging with different stresses, providing a strong evidence to indicate that stresses are causative factors for IBS-D. In response to stresses, many inflammatory cytokines and related signaling pathways are activated, which can affect the function of intestinal mucosa with increasing intestinal permeability or visceral hypersensitivity and eventually result in IBS-D symptoms [ 24 26 ], rather than damage the structure of intestinal mucosa. In line with these observations, our results also demonstrate that inflammatory factors, such as IL-8, TNFα, and MyD88 are significantly increased in the serum of IBS-D rats.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol (CFA+stress) produces the comorbid pain condition. We previously reported that saline injection into the masseter muscle followed by stress was similar to stress alone and CFA injection without stress did not induce visceral hypersensitivity 31,57,71 .…”
Section: Complete Freund's Adjuvant (Cfa) Injection In Masseter Musclementioning
confidence: 94%
“…Previous studies in animals have shown that stress increases visceral sensitivity 7,16,22,31,32,46,57,70,71 . The visceromotor response (VMR) is a contraction of core muscles in response to hollow organ distension recorded as a change in magnitude of the abdominal muscle EMG.…”
Section: Introductionmentioning
confidence: 97%
“…Clinical observation indicates that these debilitating pain conditions often occur concomitantly or overlap finally. They characterize common features such as significant prevalence rate in women and relationship with varying affective or cognitive influences [ 1 , 2 ]. Our previous studies showed that the mild stress with 3 day repeated forced swim (FS) induced prolonged visceral hypersensitivity in female rats with orofacial muscle inflammation, providing a preclinical animal model to investigate the mechanisms of the comorbid visceral pain like clinical IBS in patients with TMD [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…They characterize common features such as significant prevalence rate in women and relationship with varying affective or cognitive influences [ 1 , 2 ]. Our previous studies showed that the mild stress with 3 day repeated forced swim (FS) induced prolonged visceral hypersensitivity in female rats with orofacial muscle inflammation, providing a preclinical animal model to investigate the mechanisms of the comorbid visceral pain like clinical IBS in patients with TMD [ 1 , 2 ]. Regarding the fact that FMS patients are likely to suffer from other concurrent pain conditions such as TMD or headaches in clinic [ 3 ], the primary purpose of the present study was to clarify whether widespread somatic hyperalgesia also develops in animals with orofacial pain after stress, a typical characteristic observed in patients with comorbid TMD and FMS.…”
Section: Introductionmentioning
confidence: 99%